Avaliação imediata e após 6 meses da resistência de união a dentina de restaurações de resina composta classe I in vivo e in vitro - Rêgo, Heleine Maria Chagas [UNESP] (2015)
This study evaluated the bond strength of composite resin restorations submitted to different storage aging protocols, immediately and long-term (6 months). One hundred human posterior teeth were divided into five groups (n = 20) according storage aging protocol: Group, Group in vivo, Group water, Group cycling, Group water with Simulated Pulpal Pressure (PPS) and Group cycling with Simulated Pulpal Pressure. As further subdivided into two subgroups (n = 10) according to the time of storage were performed: 24 hours (24 hours in vivo 24 hours in water, 27/666 thermal and mechanical cycles) 6 months (6 months in vivo, 6 months in water and 5000/120000 thermal and mechanical cycles). After the opening of the cavity, the restoration was carried out with the use of phosphoric acid 37% (Vigodent), Single Bond 2 adhesive system (3M ESPE) and composite resin Grandio (Voco), following the lead of the manufacturers. After being held aging protocols for the storage time subgroup belonging specimens were sectioned obtaining sticks were submitted to microtensile test. Data were submitted to ANOVA two factors (aging and storage time) and then Tukey test (5%). The results for the microtensile tests were (MPa) ± SD: Group water 24 hours, 24.96 ± 0.95A; Group cycling 24 hours, 23.96 ± 0.56AB; Group in vivo 24h, 23.21 ± 1.23AB; Group cycling with PPS 24 hours, 19.49 ± 1.51BC, group cycling six months, 18.16 ± 0.80CD; Group cycling with PPS 6 months, 17.88 ± 1.25CD; Group water with PPS 24 hours, 17.65 ± 0.45CD; Group water 6 months, 16.68 ± 1.30CD; Group water with PPS 6 months, 14.33 ± 1,48D; In vivo group 6 months, 14.16 ± 1,51D. It was concluded that the different aging protocols used as storage times influence the bond strength dentin-resin